Edukasi Kesehatan Hewan Ternak bagi Peternak Sebagai Upaya Pencegahan dan Penanganan Penyakit Mulut dan Kuku pada Ternak di Pulau Nasi, Kecamatan Pulo Aceh, Kabupaten Aceh Besar, Aceh - Akhmadi; Machzula, Alfi Pramesti; Indrastata, Rafi Surya (Direktorat Pengabdian kepada Masyarakat, 2024)
Pulau Nasi has significant potential for cattle farming, but this potential has not yet been fully maximized. One of the factors contributing to the suboptimal cattle farming in Pulau Nasi is the traditional free-grazing method used in livestock rearing. Unfortunately, this method has several drawbacks, one of which is the ease of disease transmission among animals. Currently, the livestock in Pulau Nasi are facing an outbreak of Foot and Mouth Disease (FMD), a virus that affects cattle and buffaloes, which can potentially lead to death if the animals are infected. The aim of this community service activity is to enhance the community's skills in preventing and managing the spread of the FMD virus among livestock in Pulau Nasi. The activities carried out by the KKN-PPM UGM team include providing socialization to farmers and assisting in the treatment of livestock infected with FMD. The results of this activity show that the community has gained a better understanding of how to prevent and manage the spread of the FMD virus among livestock. The approach used was a qualitative method with data collection techniques including interviews, observation, and documentation.